Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41598-018-36439-4
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effects of amino acids on γ-polyglutamic acid production by Bacillus subtilis

Abstract: This paper is about study to increase the γ-PGA yield by developing new methods. The effect of various amino acids on production of γ-PGA by Bacillus subtilis Z15 was investigated. The γ-PGA yield was increased 23.18%, 12.15% and 31.46%, respectively, with 3 g/L aspartic acid (0 h), 1.5 g/L phenylalanine (0 h) and 7 g/L glutamic acid (24 h). Additonally, crude extract of glutamic acid after isoelectric crystallization (CEGA)could be a replacement for glutamate for γ-PGA production. Then, response surface metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Soybean heat treatment has been demonstrated to induce the breakdown of protein peptide bonds and the release of amino acids [16]. Moreover, previous researches also showed that the increased solubility of amino acids in the medium leads to additional acceleration of BS-induced fermentation and high protease activity [8,38]. Hence, the observed results suggest that proteases contained in BS robustly accelerated amino acid release because of the enhanced breakdown of proteins to amino acids in warm water.…”
Section: Comparison Of Phytochemical Profiles Of Ao-/bs-fermented Soymentioning
confidence: 95%
“…Soybean heat treatment has been demonstrated to induce the breakdown of protein peptide bonds and the release of amino acids [16]. Moreover, previous researches also showed that the increased solubility of amino acids in the medium leads to additional acceleration of BS-induced fermentation and high protease activity [8,38]. Hence, the observed results suggest that proteases contained in BS robustly accelerated amino acid release because of the enhanced breakdown of proteins to amino acids in warm water.…”
Section: Comparison Of Phytochemical Profiles Of Ao-/bs-fermented Soymentioning
confidence: 95%
“…Ammonium sulphate acts as a nitrogen source thus it is the main ingredient of the production medium. Cromwick & Gross et al and Zhang et al [10,36] reported that L-Glutamic acid and citric acid are the main precursor substrates for the production of γ-PGA biopolymer. Thus, in this present study both substrates were utilized.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of amino acids addition to a fermentation medium of B. subtilis Z15 has been demonstrated [39]. Increase in γ-PGA yield corresponding to 23.18%, 12.15%, and 31.46% was reported on the respective addition of 3 g/l aspartic acid (at 0 h), 1.5 g/l phenylalanine (at 0 h), and 7 g/l glutamic acid (at 24 h).…”
Section: Optimization Of Medium Compositionmentioning
confidence: 94%